Condicionantes para a aplicação da sanção administrativa de multa sobre o infrator pessoa física, no mercado de seguros privados fiscalizado pela SUSEP - Schmitt, Daniel (2016)
This paper deals with the repressive regime in the private insurance market ('MSP'), supervised by SUSEP – Superintendência de Seguros Privados. The research focus is to investigate the structure and the application of the norms that govern SUSEP's regulatory activity, regarding the application of the administrative sanction of fine on the individual offender. The administrative accountability in these cases is analyzed. For that, the theory of sanctioning is dealt with, dealing with the violation and the administrative sanction, especially the administrative penalty of fine. Some of the main principles of administrative sanctioning law are also highlighted, such as due process, lawfulness, characteristics and culpability. It also addresses the issue of relativisation of legality in special compliance regimes. These issues are displayed in an environment of sectoral regulation, therefore, contextualizing the sanctioning power of regulatory agencies. The repressive regime of the MSP is systematized. It identifies the National Council of Private Insurance (CNSP), the Resource Council of the National Private Insurance System (CRSNSP) and SUSEP. The normative archetype of the repressive regime of the MSP is presented, especially CNSP Resolution 243/11. A confrontation between SUSEP's guidelines and decisions of the CRSNSP in the opposite direction is made, regarding the imposition of the administrative penalty of fine on the individual offender, due to its administrative responsibility. At the end, as an outcome of the research, a set of constraints that ensure a more consistent application of the administrative penalty of fines on individuals - when considered as offenders in the MSP – is proposed.